Approximation queries for building energy-aware data warehouses on mobile ad hoc networks. (1st January 2012) - Lee, Hsun Ming; Méndez Mediavilla, Francis A.; Becerra, Enrique P.; Cook, James R.
This study proposes the use of approximate queries in order to improve the effectiveness and efficiency of data warehousing systems on mobile ad hoc networks (MANETs). In particular, the approach proposed shifts some computational cost, from the server to the client on the mobile network, thus increasing the power efficiency of the server. The study presents the concept of aggregate query approximation, goodness-of-fit of such approximations, and an evaluation of energy consumption.